Carbon Emission Calculation and Comparative Analysis during Last-mile Fresh Food Distribution Using Different Cooling Modes - Zhao Shouzheng; Zhu Zongsheng; Zhao Songsong; Liu Bin; Yu Jinze; Chen Cunkun (Zhileng xuebao)
The rapid development of fresh food distribution is facing significant pressure to reduce global carbon emissions. Reducing carbon emissions from last-mile distribution is important for energy conservation, environmental protection, and economic benefits. In this study, six typical cities in China are selected to analyze and evaluate the carbon emissions from ice storage and photovoltaic refrigeration in fresh food distribution using the entire life cycle method. When the design temperature in the delivery box is -5 °C, the results show that the carbon emission of six cities in the production stage for the photovoltaic refrigeration mode is higher than that of the ice storage mode. In the case of a 20-year life cycle, the total carbon emissions of the photovoltaic refrigeration mode in each city were reduced by 97.95%–98.78% compared with the total carbon emissions of the ice storage mode, and the emission reduction effect was significant. Among them, the carbon emissions from the use stage of the ice storage distribution mode contribute the most, and the carbon emissions from the production stage of the photovoltaic refrigeration distribution mode account for the most. Emission reduction benefits can be obtained in the decommissioning stage. When the design temperature in the distribution box increases from -5 °C to 0 °C, the carbon emissions of each city in the photovoltaic refrigeration mode are reduced by 17.74%–19.31%, whereas the carbon emissions in the ice storage mode are reduced by 13.21–18.79%. When the design temperature in the distribution box is increased from 0 °C to 5 °C, the carbon emissions of each city in the photovoltaic refrigeration mode are reduced by 17.03%–18.24%, whereas the carbon emissions in the ice storage mode are reduced by 15.22%–19.71%.